Medición de la Responsabilidad Social Universitaria en la Facultad de Ciencias de la Administración de la Universidad del Azuay - Castro-Rivera, María Elena; Solís-Gallegos, Eduardo Fabricio; Álvarez-Valencia, Juan Francisco (UDA AKADEM, 2021)
En el documento se presenta el diagnóstico de los factores clave, considerados mediante el modelo de RSU- URSULA y su relación con los Objetivos de Desarrollo Sostenible, en la Facultad de Ciencias de la Administración de la Universidad del Azuay, mediante investigación exploratoria- descriptiva con un enfoque mixto. Contiene, además, una revisión de fuentes de datos secundarios, investigación cualitativa y cuantitativa; en la parte cualitativa, se realizaron entrevistas a expertos y entrevistas a profundidad; para la investigación cuantitativa, se desarrollaron encuestas con los cuestionarios del modelo ya elaborado, dirigido a estudiantes, docentes, investigadores, docentes involucrados con proyectos de vinculación y personal administrativo, con cuyos resultados se propuso un modelo basado en una ponderación de factores, en el cual, se determinó qué acciones son las emergentes a realizar, en respuesta a los resultados determinados para la investigación. El resultado fue que, para la Facultad de Ciencias de la Administración, los ámbitos: gestión organizacional, formación estudiantes y docentes, cognición, participación social y formación, se encuentran en proceso de mejora en cuanto a sus acciones de Responsabilidad Social Universitaria. Palabras clave: Modelo URSULA, Objetivos de Desarrollo Sostenible, Responsabilidad Social Universitaria. Abstract Social responsibility arises when an organization becomes aware of itself, what surrounds it and its role with its surroundings, an ethical will and interest in doing the “right thing” so that the internal and external beneficiaries of the organization’s services are “ well”. Ca- rrying out “the good” will depend on the consensus and / or negotiation between the company and its actors, according to this, actions of what is known as Social Responsibility will be generated. The document presents the diagnosis of the key factors considered by means of the URSULA MSW model and its relationship with the Sustainable Development Goals, in the Faculty of Administration Sciences of the University of Azuay, through exploratory-descriptive research with a mixed approach, which contains a review of secondary data sources, qualitative and quantitative research, in the qualitative part, interviews with experts and in-depth interviews were conducted; For quantitative research, surveys were developed with the questionnaires of the model already prepared, aimed at students, teachers, researchers, teachers involved with outreach projects and administrative staff; With whose results a model based on a weighting of factors was proposed in which it was determined which actions are the emergent ones to be carried out in response to the results determined for the investigation; As a result, for the Faculty of Administration Sciences, in the areas: organizational management, student and teacher training, cognition, social participation and training, it is in the process of improvement in terms of its University Social Responsibility actions. Keywords: URSULA model, Sustainable development goals, University Social Responsibility